Smart oar blade for hydrodynamic analysis of rowing - Fuss, F. K.; Fundel, S.; Weizman, Y.; Smith, R. M. (Procedia Engineering, 2016)
A smart oar blade with piezoresistive sensors on either side was developed, calibrated, and tested hydrostatically, hydrodynamically and during rowing. The hydrostatic test down to a water depth of 0.7 m returned the correct and expected pressure values (r2 = 0.9953). In the hydrodynamic test, the peak differential pressure ranged from 100 Pa to 150 Pa, corresponding to a blade velocity and displacement of approximately 0.5 m/s and 0.5 m. In the rowing tests, the peak differential pressure was approximately 800 Pa, corresponding to a blade velocity and displacement of approximately 1.15 m/s and 0.9 m. The large displacement may result from the shape of the boat (gentlemen's skiff) and its load (3 people).